2004
DOI: 10.1093/ps/83.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Middle Ground for Philosophers and Production: Bioethics

Abstract: From the perspective of most animal scientists and producers, animal agriculture has become increasingly contentious over the last 10 to 20 years. Furthermore, our critics seem to be extremists whose views are biased and unreasonable. But guess what? The critics say the same thing about animal producers and scientists (us). So where is the middle ground and how do we get there? Should we even worry about trying to define the middle ground? Are these contentious issues a fad that will go away? Are these "extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Following this approach, then, it is suggested that appeals to rights by opponents of animal research, or to benefits, by advocates of animal research are inadequate. Whilst acknowledging the importance of polarized positions in helping define the issues, it is the middle ground between the poles of opposition and advocacy [ 52 , 53 , 54 ] which perhaps provides the more insightful opportunities for understanding and guiding human-animal relationships. If the middle ground between advocacy and opposition to animal research is where the relationship between animals and man flourishes, in the true spirit of co-evolution, then it is suggested that that is where the ethics of animal experimentation should be drawn from and debated.…”
Section: Difficulties With Common Ethical Stancesmentioning
confidence: 99%
“…Following this approach, then, it is suggested that appeals to rights by opponents of animal research, or to benefits, by advocates of animal research are inadequate. Whilst acknowledging the importance of polarized positions in helping define the issues, it is the middle ground between the poles of opposition and advocacy [ 52 , 53 , 54 ] which perhaps provides the more insightful opportunities for understanding and guiding human-animal relationships. If the middle ground between advocacy and opposition to animal research is where the relationship between animals and man flourishes, in the true spirit of co-evolution, then it is suggested that that is where the ethics of animal experimentation should be drawn from and debated.…”
Section: Difficulties With Common Ethical Stancesmentioning
confidence: 99%
“…Broad, popular support usually means that doctrinally motivated groups with strong underpinning values and clarity of purpose tend to be more resilient (Cronin, 2002/3; Hoffman, 1998), even if there may be setbacks owing to successful counter-measures (Hoffman, 1998). Such has proved to be the case with animal rights activism, which may be set against a trend towards more humanitarian animal farming, such as the European Union’s 1999 directive banning animals from confinement production systems (Davis and Croney, 2004). This is reflected in the large segment, 67 percent, of UK public opinion that is ‘very’ or ‘fairly concerned’ about the use of animals in laboratories (Illman, 2005), and the fact that only 60 percent support the use of animals for medical research (ICM Research, 2006).…”
Section: Existing Researchmentioning
confidence: 99%